2011
DOI: 10.1614/wt-d-10-00123.1
|View full text |Cite
|
Sign up to set email alerts
|

Common Bermudagrass Seedhead Suppression and Growth Regulation with Fenoxaprop

Abstract: Options for suppressing bermudagrass seedheads in managed turfgrass systems are limited. Experiments were conducted in 2009 and 2010 evaluating the use of fenoxaprop (25, 50, 75, and 100 g ha−1) for ‘Riviera’ bermudagrass seedhead suppression and growth regulation compared to imazapic (52 g ha−1), trinexapac-ethyl (91 g ha−1) and mefluidide (561 g ha−1). In field experiments, seedhead suppression ranged from 77 to 100% for fenoxaprop and imazapic at 35 d after treatment (DAT). Comparatively, seedhead suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 32 publications
(56 reference statements)
2
6
1
Order By: Relevance
“…At 1 WAT (data not shown), less than 10% chlorosis was observed in all treatments and no differences were detected. This trend of minimal injury within 7 d of application is consistent with other studies (Brecke et al 2010;Brosnan et al 2011). At 2 WAT, there was an increase in chlorosis for all treatments (Table 3).…”
Section: Resultssupporting
confidence: 91%
“…At 1 WAT (data not shown), less than 10% chlorosis was observed in all treatments and no differences were detected. This trend of minimal injury within 7 d of application is consistent with other studies (Brecke et al 2010;Brosnan et al 2011). At 2 WAT, there was an increase in chlorosis for all treatments (Table 3).…”
Section: Resultssupporting
confidence: 91%
“…Fewer than 5 seedheads m À2 were present when treatments were initially applied on April 9, 2010, and March 29, 2011. Mowing ceased after treatment application to facilitate visual assessments of seedhead suppression similar to previous experiments (Brosnan et al 2011;McCullough et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Sublethal rates of herbicides have also been used to suppress seedhead production of desirable turfgrasses. Brosnan et al (2011) reported that imazapic at 52 g ai ha À1 suppressed 'Riviera' bermudagrass [Cynodon dactylon (L.) Pers.] seedhead production 80 to 96%.…”
mentioning
confidence: 99%
See 2 more Smart Citations